Leiomyoma of the tunica albuginea, a case report of a rare tumour of the testis and review of the literature - Bremmer Felix; Kessel Felix J; Behnes Carl L; Trojan Lutz; Heinrich Elmar (BMC, 2012)
Abstract Background Leiomyomas are benign tumours that originate from smooth muscles. They are often seen in the uterus, but also in the renal pelvis, bladder, spermatic cord, epididymis, prostate, scrotum or the glans penis. Leiomyomas of the tunica albuginea are extremely rare. Case presentation A 59-year-old white male has noted an asymptomatic tumour on the right side of his scrotal sac for several years. This tumour has increased slowly and caused local scrotal pain. An inguinal incision was performed, in which the hypoplastic testis, the epididymis and the tumour could be easily mobilized. Macroscopically the tumour showed a solid round nonencapsulated whorling cut surface. Histologically the diagnosis of a leiomyoma was made. Conclusion We report here a very interesting and rare case of a leiomyoma of the tunica albuginea. Leiomyomas can be a possible differential diagnosis in this area. Virtual Slides http://www.diagnosticpathology.diagnomx.eu/vs/2585095378537599